METHOD OF ORTHOGONAL FREQUENCY MANIPULATION SIGNAL WITHOUT RUPTURE OF THE PHASE FOR THE ESTIMATION OF SECURITY FROM LEAK OF SPEECH SIGNALS IN THE DIGITAL FORM - V. K. Zheleznyak; D. S. Ryabenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The optimum frequency-manipulated signal for an estimation of security of channels of information leakage in the digital form is investigated. The system of signals used for an information transfer as set of signals, united by a uniform rule of construction is considered. The optimum system of signals providing the maximum noise stability at the minimum relations of energy of bit to spectral density of capacity of noise in channels of information leakage, methods of an estimation of security of discrete systems of signals in information leakage channels are offered at influence of noise of high level of type white noise, and also a choice and a substantiation of an optimum signal which will allow to estimate security of channels of information leakage.